Lexical and grammatical cohesion analysis of “nothing like us” song lyrics: written discourse analysis - Dewi, Ni Made Sinta Cahya (Journal of Language and Pragmatics Studies, 2023)
This research aims to describe and analyze the lexical and grammatical cohesion types and identify the most common lexical and grammatical cohesion in Justin Bieber's song lyrics "Nothing Like Us". The method used is the descriptive qualitative method. The subject of this research is the words found in the song lyrics "Nothing Like Us". This research showed three lexical cohesion categories, namely repetition, synonymy, and meronymy, and three grammatical cohesion categories, particularly personal reference, demonstrative reference, and conjunction. According to the findings, the song "Nothing Like Us" lyrics contain nine different lexical cohesion types, including seven repetitions, one synonym, and one meronymy. Based on the summary of the result, repetition becomes the data's most common or dominant occurrence. Meanwhile, grammatical cohesion consists of three personal reference, one demonstrative reference, and five conjunctions. As a result, conjunctions appear to be the most frequent in the data. The goal of lexical and grammatical cohesion is to provide harmony to songs to make them more meaningful. The most common effects on listeners were repetitions deepening the song's meaning and allowing listeners to enlist their thoughts more deeply in the song.